Pengelolaan Ektrakurikuler Pembuatan Pupuk Organik Cair (POC) Di SDN Patalan 4 Kecamatan Kendal Kabupaten Ngawi Jawa Timur Tahun 2016 - Ananta, Deddy, Dr. Sofyan Anif, M.Si, Dr. Suwaji, M.Kes (2016)
Deddy Ananta Prawidya Putra. Q100150011. "Management Extracurricular The Activity to Making Liquid Organic Fertilizer In The SDN Patalan 4 in Hamlet Carat Village Patalan Subdistrict Kendal District Ngawi Province East Java". Konsentrasi Menejemen Sekolah Dasar dan AUD. Fakultas Magister Administrasi Pendidikan. Program Pasca Sarjana. Universitas Muhammadiyah Surakarta 2017. Research as a purpose to review describes the planning activities Extracurricular Organic Fertilizer Production Liquids (POC), describes the implementation of activities Extracurricular Organic Fertilizer Production Liquids (POC), describing the involvement learners and them parents on the activities Extracurricular to make Liquids Organic Fertilizer (POC) in SDN Patalan 4. Methods the used is qualitative, approach to observation, interview and documentation. The risearch used qualitative methods because considerations, First adjust the qualitative methods dealing with more if easy facts plural. Second, this method of presenting operates direct interaction researcher between the respondents. Third, thismethod more flexible and sensitive to what is happening in the field. The study was conducted based on data obtained Form: 1). Extracurricular materials Manufacture of liquid organic fertilizer (POC) made from banana stem base include: Introduction of organic fertilizer, the definition of liquid organic fertilizer (POC), Micro Organism Local (MOL), and making liquid organic fertilizer (POC); 2). Manulife Extracurricular Making POC actually on the responsibility by partisipasies SDN Patalan 4, but many children often bring the tools and materials of the house each because indeed tool which was used goods used the in their homes; 3). engagement learners grades 5 and 6 and their guardians as expected, because extracurricular feels very helpful for most big thing parents worked as farmers. Extracurricular activities in order to manufacture a liquid organic fertilizer continue to run, then and should public school parties seek: 1). Promote that Carat hamlet residents, especially has followed the activities to make Liquid Organic Fertilizer (POC) that can be made self-sustainable operates And teach shown to the citizens lie Got That may yet follow the singer activities; 2). Providing information if use on chemical fertilizer farming system in hamlet carat immediate reduced, because the making POC extracurricular activities in SDN Patalan 4 has done also different test which proves how soil degradation being experienced use due to chemical fertilizers; and 3). The need for cooperation from dense whole SDN Patalan 4 school teachers, parents and support different parties use organic fertilizer for agriculture in dukuh Carat in particular, and on Ngawi scale. Keywords: Management, Extracurricular, Liquid Organic Fertilizer.